The shack [videorecording (DVD)] - Worthington, Sam, 1976-; Spencer, Octavia; McGraw, Tim; Young, William P. (Lionsgate, 2017)
After suffering a family tragedy, Mack Phillips spirals into a deep depression causing him to question his innermost beliefs. Facing a crisis of faith, he receives a mysterious letter urging him to an abandoned shack deep in the Oregon wilderness.